2017
DOI: 10.1007/s13762-017-1432-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the indoor air quality using the individual air supply system

Abstract: Indoor air quality attracts great interest. Many dwellings are ventilated naturally. The article presents the gravity system conversion into individual air supply system, which can be equipped with air fan. This solution's impact on the interior microclimate was analyzed. The proposed solution uses the lower natural ventilation ducts sections, which are not normally used as air supply channels to bring air to the housing. Exhaust grilles were located in the adjacent rooms. Individual air supply system with swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…As a result of this, actions are undertaken to seal and thermally insulate the building fabric and partitions. These procedures restrict air exchange in a room equipped with natural ventilation [11,12]. A reduced volume of air entering a building negatively affects the indoor air quality and induces a rise in the temperature, humidity, and pollution volume.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this, actions are undertaken to seal and thermally insulate the building fabric and partitions. These procedures restrict air exchange in a room equipped with natural ventilation [11,12]. A reduced volume of air entering a building negatively affects the indoor air quality and induces a rise in the temperature, humidity, and pollution volume.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to Evola et al [6] the cost of keeping the 600 ppm of CO 2 is about the same and supports the thesis of better indoor air quality kept by double -flow DCV mechanical ventilation. As in Zender-Swiercz [33] the right CO 2 concentration is better kept by mechanical, DCV ventilation.…”
Section: Comparison Of Analysed Scenariosmentioning
confidence: 76%
“…The respondents complained about poor ventilation performance because of the lack of operable windows. The problem of inadequate ventilation has also been addressed in [13,14]. On the other hand, Aflaki et al [15] performed tests in a library building in the tropics and found that the average carbon dioxide concentration was ca.…”
Section: Introductionmentioning
confidence: 99%